The effects of baicalin in depression: preclinical evidence construction based on meta-analysis - Wang, Dan; Ren, Yu-Meng; Guo, Yi-Xuan; Zhang, Zhi-Qi; Sui, He-; Zhang, Hai-Yan (Frontiers in Pharmacology, 2024)
Background: Depression manifests as a mental disorder characterized by a low mood, suicidal tendencies, disturbances in sleep-wake cycles, psychomotor agitation, and pronounced feelings of hopelessness and anhedonia. Baicalin, a natural flavonoid compound, shows significant promise in alleviating depressive symptoms in animals. This study aims to assess the impact of baicalin on experimental models of depression. Methods: A systematic search of electronic databases was conducted using the search terms "baicalin" AND "depression" OR "depressed" OR "anti-depression". Preclinical animal models representing experimental depression were included in the analysis. The risk of bias in the included studies was evaluated using the CAMARADES tools. Results: Baicalin significantly increased sucrose preference test (SPT) [SMD= 21.31, 95%CI (16.32,26.31), P＜0.00001].mThe tail suspension test (TST) duration significantly decreased in the baicalin group compared to the model group ), P＜0.0001]. Furthermore, baicalin reduced immobility time in rats subjected to the forced swim test (FST) . Compared to the model group, baicalin treatment also significantly increased the frequency of crossings in the open field test (OFT) [SMD= 32.44, 95%CI (17.74, 47.13), P＜0.00001].Baicalin significantly improves the manifestations of depressive symptoms. The effect of baicalin against depression is exerted through its anti-inflammatory actions, inhibition of oxidative stress, regulation of the HPA axis, and restoration of neuroplasticity. Future studies will be needed to further explore how these promising preclinical findings can be translated into clinical treatment for depression.